2004
DOI: 10.1016/j.mod.2004.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Medaka as a research organism: past, present and future

Abstract: This introductory review briefly describes the history of medaka as a research organism and the previous accomplishments of the medaka field. The medaka genome project currently underway through the efforts of an international consortium, the Medaka Genome Initiative, and the future prospects for medaka research, particularly for genomic analyses, are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
112
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(121 citation statements)
references
References 50 publications
1
112
0
1
Order By: Relevance
“…In Japan, there is an extensive history of research on medaka, and more recently, this organism has been used to study vertebrate development (Shima and Mitani, 2004). Medaka make approximately 35 somites at a rate of 1 per hr at 26°C (Elmasri et al, 2004b).…”
Section: Metamerism In Other Metazoansmentioning
confidence: 99%
“…In Japan, there is an extensive history of research on medaka, and more recently, this organism has been used to study vertebrate development (Shima and Mitani, 2004). Medaka make approximately 35 somites at a rate of 1 per hr at 26°C (Elmasri et al, 2004b).…”
Section: Metamerism In Other Metazoansmentioning
confidence: 99%
“…The structure of the SC in several fishes has been reported [23,24,25,26], but its molecular components have not yet been identified in any fish. To study the SC in fish, we selected the medaka fish Oryzias latipes as an experimental system for the following reasons [27,28,29]: 1) Under artificial reproductive conditions, medaka undergoes continuous spermatogenesis and oogenesis, providing experimental materials all year round, 2) medaka spermatogenesis can be reproduced in a cell culture system [30,31,32] In this study, we cloned medaka homologs of Sycp1 and Sycp3, MeSycp1 and MeSycp3 (for medaka Sycp1 and Sycp3, respectively). Using antibodies raised against recombinant proteins, we conducted immunoblotting and immunohistochemical analyses in the testis, ovary, and isolated spermatogenic cells.…”
mentioning
confidence: 99%
“…Until recently, little experimental research has been conducted to offer concrete support to one or more of these postulated transmission models. Recently, chronic infections have been successfully induced in medaka [15][16][17]32,36], thereby establishing this as an experimental species in which to study this crucial stage of infection, and the hypothesized modes of transmission between animals. These and other related studies revealed that Mm retrieved from infected tissues were also considerably more infectious, likely because these bacteria reside in the caustic intracellular environment of host macrophages of the target organs [16,19,21,30,34].…”
Section: Introductionmentioning
confidence: 99%